2014
DOI: 10.1111/odi.12205
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition of atherosclerotic plaques

Abstract: OBJECTIVE: The association of infections such as periodontitis with atherosclerotic diseases is well documented. In spite of the high diversity of the human oral microbiota, and its close contact with the circulatory system, few oral species were detected in atherosclerotic plaques. Thus, we attempted to evaluate the microbial diversity of atherosclerotic plaques from patients with different periodontal conditions, submitted to endarterectomy by a broad-range microbial method. MATERIALS AND METHODS: Patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 54 publications
2
58
0
3
Order By: Relevance
“…Importantly, some of these bacteria have been found in the intestinal tract as expected, but also within atherosclerotic plaques 1315 , which indicates the possibility of engagement of PRRs in highly distinct microenvironments. In a metagenome-wide association study (MWAS) for atherosclerosis it was recently reported that the genus Collinsella spp .…”
Section: Microorganism-associated Molecular Patternssupporting
confidence: 58%
See 1 more Smart Citation
“…Importantly, some of these bacteria have been found in the intestinal tract as expected, but also within atherosclerotic plaques 1315 , which indicates the possibility of engagement of PRRs in highly distinct microenvironments. In a metagenome-wide association study (MWAS) for atherosclerosis it was recently reported that the genus Collinsella spp .…”
Section: Microorganism-associated Molecular Patternssupporting
confidence: 58%
“…Several recent studies have analyzed microbiota communities in human oral, gut and atherosclerotic plaques from individuals with established atherosclerosis, and have found a reproducible correlation between CVD and bacterial pathogens, including Chlamydia pneumoniae, Porphyromonas gingivalis, Helicobacter pylori and Aggregibacter actinomycetemcomitans 1215 . Importantly, some of these bacteria have been found in the intestinal tract as expected, but also within atherosclerotic plaques 1315 , which indicates the possibility of engagement of PRRs in highly distinct microenvironments.…”
Section: Microorganism-associated Molecular Patternsmentioning
confidence: 99%
“…aeruginosa and other Pseudomonas species have previously been isolated from human atherosclerotic tissue, and chronic infection with P . aeruginosa has been shown to exacerbate AS in a hypercholesterolemic rat model [13, 14, 3436]. P .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one study, the microbial diversity of atherosclerotic endarterectomy plaques (N=35) was evaluated by sequence analysis of 16s ribosomal DNA. About one third contained bacterial DNA and 23 different species/phylotypes were detected, with the periodontal pathogen Aggregatibacter Actinomycetemcomitans being detected in 20% of samples [52]. …”
Section: Studies Implicating Microbiota In Atherosclerosismentioning
confidence: 99%